Mitral valvotomy at Birendra Military Hospital - Rajbhandari, GL (Nepalese Heart Journal, 2017)
Shree Birendra Hospital is a 400 bedded referral military hosital situated in Kathmandu Nepal. It has been providing medical & Surgical services to regular and retired army personnel and tieir families, for the last 75 years. It also provides specialized services in medical and surgical sub specialties like Neuro Surgery, Cardio-thoracic surgery, Uro-surgery. Gastro-enterology surgery, Laproscopic surgery, Cardiology, Gynaecology, Neuro-Psychiatry, Nephrology & various other specialities. Diagnostic facilities are provided by advance Diagnostic facilities are provided by advance pathology and Radiology deparments (MRI CT scan, Bronchoscopy, G.I. Endoscopy, Echo-cardiocardiography etc). Cardio-Thoracic Surgery unit started its services in this hospital from the year 2050 B.S. (1994 A.D) The first Cardiac surgery started with a successful operation for a patient with mitral stenosis by closed heart surgery (closed mitral valvotomy) in the year 2051 B.S, 23 Chaitra; (6th April, 1995 A.D.). cardiac problems are not usually encountered among regular army personnel due to strict medical screening during army recruitment so cardiac surgery is generally required for family members of the serving & retired army personnel instead.